Pengaruh Internet of Things: Analisis Efektivitas Kerja, Perilaku Individu dan Supply Chain - Nofrialdi, Reski; Bimas Saputra, Ebit; Saputra, Farhan; Rinanda, Yessi (Jurnal Manajemen dan Pemasaran Digital, 2023)
Abstract: The Internet of Things is developing in many sectors, especially in the industrial and household sectors. Internet of Things is expected to be a new solution in carrying out daily activities, especially those that are closely related to objects or machines. The concept of the Internet of Things itself is developing smart technology into an object, with the goal of innovation that makes activities more effective and efficient. Examples of the application of the Internet of Things in the industrial and household sectors are: 1) automatic curtain closing, 2) automatic water taps, 3) automatic folding umbrellas, 4) and also automatic parking scan sensors. The research method at this time is a descriptive qualitative method, by obtaining data based on relevant previous research and developing according to the researchers' thoughts. The results of this study are: 1) Work Effectiveness is influenced by the Internet of Things; 2) Individual Behavior is influenced by the Internet of Things; and 3) Supply Chain is affected by the Internet of Things. Abstrak: Internet of Things berkembang di banyak sektor, terutama di sektor industri dan rumah tangga. Internet of Things diharapkan menjadi solusi baru dalam menjalankan aktivitas sehari-hari terutama yang berkaitan erat dengan benda atau mesin. Konsep Internet of Things sendiri yaitu mengembangkan teknologi pintar kedalam sebuah benda, dengan tujuan inovasi yang menjadikan kegiatan lebih efektif dan efisien. Contoh penerapan Internet of Things di sektor industri dan rumah tangga yaitu: 1) Penutup gorden otomatis, 2) keran air otomatis, 3) payung lipat otomatis, 4) dan juga sensor scan parkir otomatis. Metode Penelitian pada kali ini yaitu metode kualitatif deskriptif, dengan memperoleh data berdasarkan penelitian terdahulu yang relevan dan mengembangkan sesuai pemikiran peneliti. Hasil dari penelitian ini yaitu: 1) Efektivitas Kerja dipengaruhi oleh Internet of Things; 2) Perilaku Individu dipengaruhi oleh Internet of Things; dan 3) Supply Chain dipengaruhi oleh Internet of Things.